1996
DOI: 10.1007/s002239900107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous glucocorticoid infusion on bone metabolism in the rat

Abstract: The effects of continuous administration of supraphysiologic doses of dexamethasone (DEX) on bone metabolism were examined in rats. Adult, male, Sprague Dawley rats were infused with DEX at a constant rate of 16.25 microg/day for 19 days. Despite soft tissue catabolism, DEX treatment led to a significant increase in bone volume in all experiments. This was accompanied by a significant gain in femoral weight and calcium content. These findings were also observed in DEX-treated parathyroidectomized animals indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…In the present study, however, the administration of mPSL for 4 weeks dose-dependently increased the BMD of the tibial metaphysis in rats. Although our present findings were contrary to previous findings in humans and in certain animal species (8 -12, 22, 23), they are consistent with the data from previous studies using rats that showed increased bone mass or BMD after the treatment with GCs (24,25,33,34).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In the present study, however, the administration of mPSL for 4 weeks dose-dependently increased the BMD of the tibial metaphysis in rats. Although our present findings were contrary to previous findings in humans and in certain animal species (8 -12, 22, 23), they are consistent with the data from previous studies using rats that showed increased bone mass or BMD after the treatment with GCs (24,25,33,34).…”
Section: Discussionsupporting
confidence: 69%
“…A recent study by Okazaki et al (26) demonstrated that the administration of prednisolone prevented a decrease in bone mass in rats with adjuvant-induced arthritis by reducing the increase in bone resorption and the decrease of bone formation at both the local and systemic levels. King et al (24) and Turner et al (25) also reported that treatment with dexamethasone or prednisone increased the bone mass in normal rats or ovariectomized rats, which might be due to a greater suppression of resorption rather than formation. In contrast to the increase in BMD in the metaphysis, BMD in the tibial diaphysis decreased in a dose-dependent fashion (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Numerous previous papers have reported that high- dose steroids suppress bone resorption in rats (Jee et al 1970;King et al 1996;Kondo et al 2006). Our histological findings were consistent with those previous studies.…”
supporting
confidence: 93%
“…For example, markers of bone turnover may reflect changes in bone metabolism induced by oophorectomy (57,125), hyperparathyroidism (126,127), Paget's disease (128), physical exercise (129), immobilisation (32,130), alcoholism (131), smoking (132), vitamin D deficiency (33,35,37,133), chronic inflammatory bowel disease (134,135), chronic starvation (136), thyroid disorders (52,137) as well as the pharmacological effects of glucocorticosteroids (48,139,140), androgens (6,7,141), gonadotropin-releasing hormone agonists (142), warfarin (143), growth hormone or insulin-like growth factors (144). Bone turnover markers may be useful in the diagnosis and management of certain of the above conditions, but in most cases has not been rigorously examined.…”
Section: Other Conditionsmentioning
confidence: 99%